PURCHASE INTENTION TOWARD LOCAL SKINCARE - Wijaya, Marchellia; Tjokrosaputro, Miharni (International Journal of Application on Economics and Business, 2024)
Currently, the need for body and facial care has become a community need because the emergence of various skin problems in women has prompted many local businesses to develop products to address them. This study used a non-probability method with a purposive sampling technique, as many as 224 respondent data were obtained through online questionnaires using the Google form and the data was analyzed using SmartPLS4.0-SEM. The results in this study were conducted with the aim of testing the attractiveness and trustworthiness of the purchase intention of local skincare products mediated by brand image. This study used a purposive sampling method, population data for this study were taken from samples who live in Jakarta and know about skincare local products as many as 296 valid individuals out of a total of 337 individuals and were obtained through online questionnaires using the Google form and data were analyzed using SmartPLS-SEM are valid. The result of this study is that attractiveness and trustworthiness can influence purchase intention which is mediated by brand image.